Exploring the Didactic and Epistemic Risks of Incorporating the Children's Perspective in School History: Didactic Guidelines for Active Teachers - Álvarez Sepúlveda, Humberto Andrés (2023)
Although the children's perspective can contribute to enrich the teaching of the contents present in the Chilean history curriculum and in the school texts of this subject, it is essential to be cautious about the following three didactic and epistemic aspects in its implementation in order to develop historical thinking in students: 1) the risk of generalizing childhood as an abstract category; 2) the possible danger of promoting social stereotypes against the adult world; and 3) the scarce development of historical knowledge about childhood. As a result of these problems, this essay presents a hermeneutic analysis that aims to substantiate these risks to establish consistent didactic and epistemological guidelines when integrating the perspective of children in the history classroom. Methodologically, this work is backed by a scoping review of normative documents of the Chilean History, Geography, and Social Sciences curriculum and publications hosted in different databases (Latindex, Wos, Scopus, Scielo, Clacso, Redalyc, ProQuest, and Dialnet). Moreover, the author conducted this paper under the inductive method, the humanistic paradigm, with a qualitative approach, interpretative type, and topical narrative design. Therefore, as a conclusion, it is necessary to advance towards a critical curriculum that considers the teaching of childhood in history; however, to do so, society needs to overcome several obstacles associated with the predominance of technical curricular rationality and the current educational policy in Chile.